IMPROVING THE EFFICIENCY OF METROLOGICAL SUPPORT FOR SCIENTIFIC RESEARCH - Doniyev, Erkin Tangimuratovich; Maxmonov, Uktam Ashirovich (SCIENCE and SOCIETY, 2026)
Metrological support is of particular importance in scientific research. Measurement errors that occur during experiments not only negatively affect the results of research, but also lead to erroneous conclusions, negatively affect the quality and effectiveness of the completed scientific research work. This article outlines some of the problems of metrological support that currently arise during research and development work and proposals aimed at eliminating them.
Keywords: metrological supply; measurement tools; test tools; ensuring accuracy of measurements; unity of measurements; metrological support in research works